Fourteen cases of imposed upper airway obstruction. Issue 2 (February 1992) - Samuels, M P; McClaughlin, W; Jacobson, R R; Poets, C F; Southall, D P
Abstract : Imposed upper airway obstruction was diagnosed as the cause of recurrent and severe cyanotic episodes in 14 patients. Episodes started between 0.8 and 33 months of age (median 1.4) and occurred over a period of 0.8 to 20 months (median 3.5). Diagnosis was made by covert video surveillance, instituted after either (a) the observation that episodes began only in the presence of one person, or (b) characteristic findings on physiological recordings, lasting between 12 hours and three weeks, performed in hospital or at home. Surveillance was undertaken for between 15 minutes and 12 days (median 24 hours) and resulted in safety for the patient and psychiatric assessment of the parent: mother (n = 12), father (n = 1), and grandmother (n = 1). These revealed histories of sexual, physical, or emotional abuse (n = 11), self harm (n = 9), factitious illness (n = 7), eating disorder (n = 10), and previous involvement with a psychiatrist (n = 7). Management of the abusing parents is complex, but recognition of their psychosocial characteristics may allow earlier diagnosis. Imposed upper airway obstruction should be considered and excluded by physiological recordings in any infant or young child with recurrent cyanotic episodes. If physiological recordings fail to substantiate a natural cause for episodes, covert video surveillance may be essential to protect the child from further injury or death.